1997
DOI: 10.1139/m97-077
|View full text |Cite
|
Sign up to set email alerts
|

Correlation ofPseudomonas aeruginosavirulence factors from clinical and environmental isolates with pathogenicity in the neutropenic mouse

Abstract: The potential pathogenicity of a microorganism is a major concern for Health Canada evaluators, who will be processing new biotechnology products under the Canadian Environmental Protection Act. Potential pathogenicity is generally predicted by the results of animal pathogenicity studies. In an attempt to define surrogate data for an animal model, this study was initiated. Pseudomonas aeruginosa isolates from clinical and environmental sources were screened for their pilus type, serotype, lipopolysaccharide ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Observations from clinical experience and a number of infectious models indicate that the virulence of P. aeruginosa varies from strain to strain (32,48,51,60), although the mechanisms accounting for this variation are not completely understood. The genes of most of the characterized P. aeruginosa virulence determinants are located in the core genome and therefore present in all strains (59).…”
mentioning
confidence: 99%
“…Observations from clinical experience and a number of infectious models indicate that the virulence of P. aeruginosa varies from strain to strain (32,48,51,60), although the mechanisms accounting for this variation are not completely understood. The genes of most of the characterized P. aeruginosa virulence determinants are located in the core genome and therefore present in all strains (59).…”
mentioning
confidence: 99%
“…Possibly, the MAR strain thus was less virulent for the 4 patients, i.e., remained localized in the lower respiratory tract and failed to spread and disseminate [72]. As expected [73], the combined blood/ antibiotic time kill curve assays revealed the combination of amikacin and fosfomycin with added blood to be effective against the two MAR isolates 125 and 127 (table 9).…”
Section: Discussionmentioning
confidence: 80%
“…Different in vitro biofilm forming capacities and reduced ability of lung colonization was observed in environmental isolates as compared to clinical isolates by Head and Yu (22). However Woods et al (31) were not able to differentiate both the isolates on the basis of correlation of production of extracellular enzymes and LD50. In this study, we have observed that environmental isolates differ from clinical isolates with respect to their outer membrane protein profiles and their ability to establish in the urinary tract of mouse.…”
Section: Resultsmentioning
confidence: 95%